Evaluation of boron nitride nanoparticles on delamination in drilling carbon fiber epoxy nanocomposite materials - KAYNAK, YUSUF (SAGE PUBLICATIONS LTD, 2020)
The reinforcements of nanoparticles have an important role in improving the machinability of nanocomposite materials. Except for the known nanoparticles such as carbon nanotube, graphene, nanoclay, etc., the effect of boron nitride reinforcement on the machinability of composite materials are a recent research topic. In this study, boron nitride nanoparticle was introduced to the matrix resin that brings about additional strength and enhancement in thermal and mechanical properties of the composite. Though it was confirmed that this composition enhances the focused properties, it is necessary to investigate drilling performance of these composite and identify the effects of this boron nitride nanoparticle on machinability of carbon fiber epoxy nanocomposite considering thrust force, delamination factor, etc. Accordingly, while the thrust force is increased by reinforcement of the boron nitride nanoparticles, on the contrary of literature, delamination factor is tend to reduce as compared with reference composite. This experimental study shows the addition of boron nitride nanoparticles help to reduce delamination factor of carbon fiber epoxy nanocomposite. In addition, hole surfaces and drilling mechanism analyzed with optical and scanning electron microscope about damage estimation.
Keywords: Drilling; carbon fiber; boron nitride nanoparticle; nanocomposite; delamination; thrust force; cutting; REINFORCED PLASTICS; SURFACE-ROUGHNESS; THRUST FORCE; HYBRID NANOCOMPOSITES; POLYMER COMPOSITES; PROCESS PARAMETERS; TOOL GEOMETRY; HIGH-SPEED; CFRP; MATRIX